The implementation of digital storytelling using discovery learning in EFL listening class: middle school students’ and teachers’ voices - Langgeng Budianto; Minatul Azmi; Alam Aji Putera (Journal on English as a Foreign Language, 2021)
Due to the rapid elevation of technology, teachers are expected to integrate technology into the classroom to engage students considered digital natives. Digital storytelling is an alternative medium for teaching listening skills. This case study investigated students’ and teachers' voices of the implementation of digital storytelling using discovery learning. An in-depth interview, classroom observation, and open-ended questionnaire were applied to explore the implementation of digital storytelling using discovery learning. This case study involved a middle school English teacher and 30 students from a junior high school level in Bali, Indonesia. The qualitative data from students and teachers interviews and observations showed that the students perceived that digital storytelling is more engaging, interesting, and motivating to improve their listening skills. The most challenging activities rested on students' limited vocabulary during the communication stage using Bahasa Indonesia. The pedagogical implication of this study is that EFL teachers need to provide learners with relevant vocabulary to support learners' communication skills during the classroom session during the implementation of digital storytelling. Since learners' limited vocabulary becomes one of the hindering factors in teaching listening, it is recommended for a further researcher to address this issue.